Merriman's asessment of the lower limb - Yates, Ben 1967; Merriman, Linda M. (Churchill Livingstone Elsevier, 2012)
ASSESSMENT OF THE LOWER LIMB is the benchmark textbook of lower limb examination and assessment. The third edition preserves the lucidity, logical approach and comprehensive coverage of its predecessors but adds many new exciting features, including an all-new design, new contributors, thorough updating of all chapters - many of which have been completely rewritten - and an entirely new chapter on functional assessment. The DVD provides extensive videos of assessment techniques and illustrations: practitioners with patients and models show how to assess all parts of the lower limb, and evaluate various conditions